Investigating the Emotional and Social Factors, Affecting Motivation, Self-Esteem and Self-Efficacy. The Case of Second Year Students at 18 February Secondary School in Merahna Souk-Ahras - BEDAIRIA Rayene (My University, 2024)
formulaireAbstract The study examines the intricate relationship between emotional and social factors and their impact on the motivation, self-efficacy, and self-esteem of students at the 18 February Secondary School in Merahna – Souk Ahras. Aiming to test the main hypotheses, this research utilized a mixed method to collect both quantitative and qualitative data (Qualitative: non-participant classroom observation, interview. Quantitative: student’s questionnaire). Initially, a questionnaire involving 5 sections was administered to 51 students from the 18 February Secondary School in Merahna. Secondly, a non-participant classroom observation was conducted during the second term (school year 2023-2024) with the second-year literary class at 18 February Secondary School. Thirdly, a structured interview was conducted with two English teachers from the same secondary school. The gathered data have illustrated that emotional and social factors play a crucial role in influencing students’ motivation, self-beliefs, and academic performance in secondary school. Therefore, the first hypothesis was confirmed ------------------------ ملخص تتعلق الدراسة بفحص العلاقة المعقدة بين العوامل العاطفية والاجتماعية وتأثيرها على الدافعية والكفاءة الذاتية وتقدير الذات لدى طلاب ثانوية 18 فبراير في المراهنة - سوق أهراس. بهدف اختبار الفرضيات الرئيسية، استخدمت هذه الدراسة أسلوبًا مختلطًا لجمع البيانات الكمية والنوعية. في البداية، تم تنفيذ استبيان يتضمن 5 أقسام لـ 51 طالبًا من ثانوية 18 فبراير في المراهنة. ثانيًا، تم إجراء ملاحظة غير مشاركة في القسم خلال الفصل الدراسي الثاني (السنة الدراسية 2023-2024) مع الفصل الأدبي للسنة الثانية في ثانوية 18 فبراير. ثالثًا، تم إجراء مقابلة منظمة مع مدرسين اثنين للغة الإنجليزية من نفس المدرسة الثانوية. أظهرت البيانات المجمعة أن العوامل العاطفية والاجتماعية تلعب دورًا حاسمًا في التأثير على دافعية الطلاب واعتقاداتهم الذاتية والأداء الأكاديمي في المدرسة الثانوية. لذلك، تم تأكيد الفرضية الأولى ------------------------- Résumé L'étude porte sur l'examen de la relation complexe entre les facteurs émotionnels et sociaux et leur impact sur la motivation, l'auto-efficacité et l'estime de soi des élèves du lycée 18 Février à Merahna – Souk Ahras.. Dans le but de tester les hypothèses principales, cette recherche a utilisé une méthode mixte pour collecter à la fois des données quantitatives et qualitatives. Initialement, un questionnaire comprenant 5 sections a été administré à 51 élèves de l'école secondaire du 18 février à Merahna. Deuxièmement, une observation de classe non participante a été menée pendant le deuxième trimestre (année scolaire 2023-2024) avec la classe littéraire de deuxième année à l'école secondaire du 18 février. Troisièmement, une entrevue structurée a été réalisée avec deux enseignants d'anglais de la même école secondaire. Les données recueillies ont illustré que les facteurs émotionnels et sociaux jouent un rôle crucial dans l'influence sur la motivation des élèves, leurs croyances en eux-mêmes et leur performance académique au lycée. Par conséquent, la première hypothèse a été confirmée.